The cost of treating paediatric malaria admissions and the potential impact of insecticide-treated mosquito nets on hospital expenditure. - Kirigia, J; Snow, R; Fox-Rushby, J; Mills, A (1998)
OBJECTIVE: To calculate the costs at Kilifi District Hospital (KDH) and Malindi Sub-district Hospital (MSH) of treating paediatric malaria admissions including three common presentations of severe paediatric malaria, i.e. cerebral malaria, severe malaria anaemia and malaria-associated seizures; and to estimate the implications for hospital expenditure of a reduction in paediatric malaria admissions. METHODS: Patient data were obtained from hospital records. All costs were allocated to departments that provided direct patient care by a four-stage step-down procedure. Laboratory and drug costs of treating paediatric malaria admissions were separately identified. RESULT: Unit recurrent costs per admission in KDH ranged from US $57 for 'other' paediatric malaria to US $105 for cerebral malaria, and in MSH from US $33 to US $44 for the same categories. The annual recurrent cost of treating all paediatric malaria admissions to KDH prior to the trial was estimated at US $78 900. Adjusting for preintervention differences in malaria admission rates and age between intervention and control areas, the ITBN trial found a 41% reduction in paediatric malaria admissions. The reduction in admissions resulted in an estimated saving of US $6240 in the cost of treating paediatric malaria admissions from the intervention area. CONCLUSION: There would be a substantial reduction in costs of treating paediatric malaria admissions if the intervention were introduced in the whole catchment area of the hospital. Actual savings would depend on the proportion of potential savings that can in practice be realised, and on the effectiveness of the intervention when routinely implemented.